2017
DOI: 10.24925/turjaf.v5i9.1080-1085.1291
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Composition and Antioxidant Activity of Tricholoma Imbricatum and T. Focale

Abstract: Edible mushrooms are one of the important food source because of their tastes, and having high concentration of fatty acids and the other nutrients. In this study, fatty acid composition and antioxidant properties of Tricholoma imbricatum and T. focale were determined. The fatty acids were analysed by GC, and GC-MS while the antioxidant activity was tested using five complimentary methods; namely, β-carotene-linoleic acid, DPPH scavenging, ABTS scavenging, CUPRAC and metal chelating assays. Eight fatty acids w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…(2008) reported the antioxidant activity of the extracted flavonoids from M. paradisiaca in rats. According to GC‐MS results of the extract, the presence of vitamine E and palmitic acid, which are already known to possess high antioxidant activities, may be related to the greater antioxidant activity (Almeida et al., 2012; Elagbar et al., 2016; Kaplaner et al., 2017; Varvařovská et al., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…(2008) reported the antioxidant activity of the extracted flavonoids from M. paradisiaca in rats. According to GC‐MS results of the extract, the presence of vitamine E and palmitic acid, which are already known to possess high antioxidant activities, may be related to the greater antioxidant activity (Almeida et al., 2012; Elagbar et al., 2016; Kaplaner et al., 2017; Varvařovská et al., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Decrease in the red color of the complex ferrozine-Fe 2+ indicates high radical scavenging activity of the compound. 23 To compare the effect of aqueous, acetonic extracts and standard (EDTA), the values of IC 50 were calculated, which demonstrated that EDTA possess the most powerful chelating activity (IC 50 = 6.273± 0.288 µg/mL) followed by the aqueous extract (IC 50 = 128.155±5.887 µg/mL). However, the acetonic extract didn't reach 50% chelating activity and presents maximal activity of 41.433±2.518 % at 468.75 µg/mL.…”
Section: Metal Chelating Activitymentioning
confidence: 99%
“…In this test, the antioxidants give hydrogen molecules to the media which stops the peroxidation of linoleic acid, the hydrogen also scavenge singlet oxygen responsible of linoleic acid peroxidation. 23 The lowest β -carotene discoloration rate exhibited the highest antioxidant activity, Figure 6 shows the lipid peroxidation inhibitory activity of M. rotundifolia extracts by the β carotene-linoleic acid assay. The inhibition ratios of the oxidation of linoleic acid by the acetonic and aqueous extracts, were giving approximately the same percentage of inhibition ratio, 79.778± 1.812% and 84.666± 0.963 % respectively.…”
Section: β-Carotene/ Linoleic Acid Bleaching Assaymentioning
confidence: 99%